A Feasibility study on cement bonded boards made from sugarcane bagasse - Bernarte, Alfredo L., Jr.; Bides, Emmuel John T.; Melendres, Paolo Enrico A.; Usison, Silverio Manuel B. (Diliman, Quezon City College of Engineering, 1997)
The project under study is the commercial production of Cement Bonded Boards made from Sugarcane Bagasse. This product is intended to become a major substitute for plywood and other panel products. CBB's are made from cement and bagasse flakes that are cold pressed to form panel boards. Such boards exhibit superior characteristics such as termite, rot, fire and, to certain extent, water resistance. this study is segregated into three main parts namely; Market study, Technical study, Financial and Social Profitability study. The Market study deals with all aspects presently affecting the potential of such a venture; market viability, market share as well as present supply and demand trends were also taken into account. The targeted market share after the first five years of operation is 10% from the initial year's 3%. This translates into demand for panel boards from 200,000 in the first year to 1,125,000 boards towards becoming a sunshine industry in the country. The technical study takes into account all aspects of production of Cement Bonded Boards. The target level of production is based on the estimated demand as calculated from the previous market study and work is conducted for 16 hours each day with two shifts. There would be 305 workdays per year with 58 direct production personnel. All equipment that are going to be used for production were evaluated according to their merits and total cost of production equipment sums to P 5.05 million. The plant will be located in Bgy. Telebastagan, San Fernando, Pampanga, an agro-industrial area fit for labor intensive plants such as this. Total Project Cost reaches P 62.092 million for the project. Based on the given technical analysis, the project is deemed technically feasible in the Philippine setting. The financial study evaluates the proposed setup as to cash flow requirements, liquidity and debt requirements, as well as the possible avenues for acquiring the needed capital. Financing is provided by the Development Bank of the Philippines in the amount of P 45 million with the owners providing their personal properties as collateral in order to secure the special financing scheme. Net Present Value of the Project amounted to P 170 million, almost thrice the initial investment after only five years. Internal Rate of return gives a 37% interest rate as compared to 14-21% returns with bank and government securities and the payback period is approximately 3.2 years. The initial year sees a Net Income of P 7.2 million. With a sound basis such as these, the financial aspect of the project is deemed viable. Lastly, the company will be registered as corporation with 36 administrative personnel and 58 direct production laborers. This project would definitely benefit the community where it would be operating in as to that community's employment opportunities including possible downstream industries. Such are among the possible benefits of putting up a Cement Bonded Board Plant in the country and with this, the group concludes that the project is indeed truly feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Sugarcane products; Cement industries; Bagasse; Cement composites; Participatory monitoring and evaluation (Project management)